Clinical explainable differential diagnosis of polypoidal choroidal vasculopathy and age-related macular degeneration using deep learning. (April 2022) - Ma, Da; Kumar, Meenakshi; Khetan, Vikas; Sen, Parveen; Bhende, Muna; Chen, Shuo; Yu, Timothy T.L.; Lee, Sieun; Navajas, Eduardo V.; Matsubara, Joanne A.; Ju, Myeong Jin; Sarunic, Marinko V.; et al.
Abstract: Background: This study aims to achieve an automatic differential diagnosis between two types of retinal pathologies with similar pathological features - Polypoidal choroidal vasculopathy (PCV) and wet age-related macular degeneration (AMD) from volumetric optical coherence tomography (OCT) images, and identify clinically-relevant pathological features, using an explainable deep-learning-based framework. Methods: This is a retrospective study with data from a cross-sectional cohort. The OCT volume of 73 eyes from 59 patients was included in this study. Disease differentiation was achieved through single-B-scan-based classification followed by a volumetric probability prediction aggregation step. We compared different labeling strategies with and without identifying pathological B-scans within each OCT volume. Clinical interpretability was achieved through normalized aggregation of B-scan-based saliency maps followed by maximum-intensity-projection onto the en face plane. We derived the PCV score from the proposed differential diagnosis framework with different labeling strategies. The en face projection of saliency map was validated with the pathologies identified in Indocyanine green angiography (ICGA). Results: Model trained with both labeling strategies achieved similar level differentiation power (>90%), with good correspondence between pathological features detected from the projected en face saliency map and ICGA. Conclusions: This study demonstrated the potential clinical application of non-invasive differential diagnosis using AI-driven OCT-based analysis, with minimal requirement of labeling efforts, along with clinical explainability achieved through automatically detected disease-related pathologies. Highlights: We presented our study to achieve an automatic differential diagnosis of PCV and AMD from non-invasive volumetric OCT Different B-scan-level predictions and aggregation strategies showed similar differentiation power en face projection of aggregated Grad-CAM demonstrated good correspondence with the corresponding fundus angiography